The Influence of Audit Experience and Task Complexity on the Quality of Auditor Performance : (Study at Public Accounting Firms in Bali Province) - Ida Ayu Sari Wisastry; I Gusti Ayu Nyoman Budiasih (International Journal of Economics and Management Sciences, 2024)
This research aims to obtain empirical evidence of the influence of audit experience and task complexity on the quality of auditor performance. The population used in this research were all auditors at Public Accounting Firms in Bali Province. The sampling technique was through purposive sampling, so that the sample size was 19 KAPs with all auditors as research respondents. This research uses the Multiple Regression Analysis technique. The output of multiple regression analysis shows that audit experience has a positive effect on the quality of auditor performance and task complexity has a negative effect on the quality of auditor performance. The implications of this research can be used as a guide to pay attention to audit experience and task complexity, so that it can improve the quality of auditor performance and can also have a positive impact on Public Accounting Firms.